The use of modern multibody-simulation (mbs) software in biomechanical education - Schiebl, F. (International Journal of Computer Science in Sport, 2003)
The paper addresses possibilities of using modern multibody-system (mbs) software in sports biomechanical education. Several prototypical models with different complexity will be described. The first type contains mechanical models which can be used to clarify mechanical laws. This models are not of necessity biomechanical models. Another type deals with simple basic models of sporting movements and the third type handles complex mechanical models of living systems. Each of this models is suitable for different purposes in biomechanical education. The use of mbs-software simplifies the modelling but there are some risks which have to be discussed.